Hubungan Antara Kepuasan Kerja dan Budaya Organisasi di Perpustakaan Tunku Tun Aminah, UTHM - Ismail, Nur Afiah; Shamsuddin, Alina (Research in Management of Technology and Business, 2020)
Job satisfaction and organizational culture are very important for an organization in creating an organization that is competitive in terms of economic, social, political and technological. It includes factors that influence job satisfaction and organizational culture. This survey was conducted due to the lack of research on the relationship of job satisfaction to organizational culture in the public education sector in Malaysia. Therefore, this study aims to identify job satisfaction in the organization and also identify the organizational culture in the Tunku Tun Aminah Library, UTHM. This study also wanted to identify the relationship between job satisfaction and organizational culture. Quantitative methods were used in this study. The study population was 80 people. Questionnaires were distributed to 70 employees at Tunku Tun Aminah Library, UTHM to obtain information. Data analysis used Statistical Package for Social Science (SPSS) 22 for spearman correlation analysis. This study gives importance to the staff at Tunku Tun Aminah Library, UTHM and also the university administration in increasing work productivity. The results of the study show that there is a positive relationship between job satisfaction and organizational culture.